Factors associated with knowledge of mother-to-child transmission (MTCT) of HIV/AIDS among young adults in Indonesia: Analysis of IYARHS - Maretalinia; Buston, Erni; Nurmalita Sari, Marlynda Happy; Nuraeni, Tating; Sulyastini, Ni Komang; Sholihat, Siti (Public Health of Indonesia, 2023)
Background: The prevalence of mother-to-child transmission (MTCT) of HIV/AIDS is increasing, particularly in low- and middle-income countries. Most previous studies focused on pregnant women in antenatal care, but this study examined the early phases of non-married women, which are young adults. Objective: This study aimed to examine the factors associated with knowledge MTCT of HIV/AIDS among young adults in Indonesia. Methods: This study used secondary data from the Special Indonesia Demographic Health Survey (IDHS), also known as the Indonesia Young Adult Reproductive Health Survey (IYARHS). The unit of analysis in this study is a non-married young adult aged 14 to 24 from 34 provinces in Indonesia. The final samples brought into the analysis were 9,600 women. The univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using binary logistic regression were done using the STATA 17 version licensed by the Institute for Population and Social Research, Mahidol University. Results: This study revealed that 33.75% of the respondents had poor knowledge of the MTCT of HIV/AIDS. Moreover, the factors found to be significantly associated with knowledge of MTCT of HIV/AIDS were age (19 to 24 years old), residence in an urban area, graduation from junior high school, senior high school, academy, and university, and also those who talked about sexual matters with friends. Conclusion: This study suggests supporting and encouraging related stakeholders in order to provide education about MTCT in the early years of adulthood so the prevention program can be applied more easily.